Technical or Operational Aspects of Vannamei Shrimp Business Plan - Arif Darmawan, Nugroho; Fitrianto, Hendry; Kustiawan, Unggul (Dinasti Publisher, 2025)
In a Vannamei shrimp farming business plan, the operational plan aspect is the main foundation that organizes all business activities in a structured and measurable manner, starting from the establishment stage to projected operational costs. This process begins with site preparation, procurement of production facilities, equipment, and licensing, as a legal and technical foundation for optimal farming (Budi, 2020). Next, operational goals and objectives are set, including production targets, shrimp size, and harvest quality standards, which form the basis for technical and resource arrangements (Asmara et al., 2021). Operational design includes RAS-based intensive culture systems, water quality management, feeding schedules, disease control, as well as the number of workers and utilization of supporting technology (Surianti et al., 2024). The operational delivery phase is carried out according to standard schedules and procedures, with regular monitoring of water quality, shrimp health and growth, and recording of operational data (Prakoso & Riani, 2019). Projected operational costs include all production components, such as fry, feed, labor, electricity, water, and maintenance, with a focus on efficiency to maintain profitability (Saputra et al., 2019). With a systematic operational plan, Vannamei shrimp farming is expected to be efficient, sustainable and profitable